Designing for Lived Informatics in Out-of-Clinic Physical Rehabilitation. (2nd January 2018) - Bagalkot, Naveen L.; Sokoler, Tomas
Abstract : In this article we focus on how rehabilitees make use of personal data as part of performing their prescribed physical therapy in out-of-clinic settings (e.g., home). Over the past 5 years we have been extensively involved in the design of pervasive and mobile technologies to support out-of-clinic physical rehabilitation. Two strands guide our work: situated and embodied interaction, and the practice and theory of physical rehabilitation. In particular we draw upon the latter's practice of integrating therapy with the lived everyday settings and the model of Person–Environment–Occupation. We revisit this work from the emerging perspective of lived informatics to bring forward multiple instances of rehabilitees using personal rehabilitation data to make sense of their physical rehabilitation process. We present these instances under four categories: becoming your own standard of reference; marking your life as a rehabilitee; articulating with therapists, partners, and peers; and incorporating exercising with everyday activities. We put forward the Person–Environment–Occupation model as a generative entry point for designing digital technology in support of lived informatics in out-of-clinic physical rehabilitation. Through this article we invite researchers in the field of lived informatics to engage in the design of digital technologies for out-of-clinic physical rehabilitation.